Effect of Information, Education, and Communication activity on health literacy of cardiovascular diseases among school-going adolescents in Delhi - Srishti Yadav; Anita Khokhar (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Heart attack and stroke account for >80% of deaths due to cardio-vascular diseases (CVDs) in India. Adolescents are the most susceptible group to adopt risky behaviors causing CVDs such as use of tobacco and alcohol, sedentary lifestyle, and unhealthy diet. This study was conducted to assess the health literacy of CVDs such as heart attack and stroke among school-going adolescents and change in health literacy after different information, education, and communication (IEC) activities. MATERIALS AND METHODS: It was a school-based interventional study conducted in two schools among students of classes 6, 7, and 8. The educational interventions were done in the form of pamphlets, posters, and lectures on heart attack and stroke. The postintervention data were collected 2 weeks after the first intervention and 3 months after the last intervention. RESULTS: There were a higher proportion of students with satisfactory level of knowledge of heart attack and stroke both at 2 weeks and 3 months after the interventions in both the schools, and the results were statistically significant (P < 0.05). CONCLUSION: The health literacy regarding CVDs has improved when compared to baseline after IEC activities among school-going adolescents.